The Effect of Carbon Emission Disclosure and Green Investment on Firm Value - Ni Wayan Sulistiani; Made Yenni Latrini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Firm value is a crucial indicator that provides information to investors for making investment decisions. Today, investors also consider a company’s commitment to environmental issues, especially in the energy sector, which significantly contributes to carbon emissions. This study aims to empirically examine the effect of carbon emission disclosure and green investment on firm value. The theoretical framework employed includes signaling theory and legitimacy theory. Firm value is measured using the Tobin’s Q ratio. Carbon emission disclosure is measured through content analysis based on the GRI 305 standards, while green investment is measured using the PROPER rating issued by the Ministry of Environment and Forestry. This study also includes three control variables: firm size, leverage, and profitability. The analytical method used is multiple linear regression, with secondary quantitative data collected from companies’ annual reports and sustainability reports. The sample consists of 69 companies with a total of 271 observations. The findings reveal that carbon emission disclosure has a positive effect on firm value, while green investment does not have a significant effect on firm value. This research is expected to contribute to the development of signaling and legitimacy theories and serve as a practical reference for investors in considering environmental aspects when making investment decisions.